التوجيه اللغوي لانفرادات أبي عمرو في القراءة - حمده, نور الدين; طواهرية, عمر (University of Eloued-جامعة الوادي, 2022)
"هذه دراسةٌ بعنوان: التوجيه اللّغوي لانفرادات الإمام أبي عمرو البصري في القراءات القرآنية. والإشكال المطروح: إلى أيّ مدى اهتمّ العلماء بانفرادات أبي عمرو البصري في القراءة؟، وما مستويات توجيههم لهذه الانفرادات لغوياًّ؟ والخطّة المُتّبعة في إنجازها على النّحو التالي: المبحث الأوّل: مدخلٌ مفاهيمي. وينقسم إلى مطلبين: المطلبُ الأوّل: أبو عمرو بن العلاء البصري؛ حياته الشخصية والعلمية. المطلبُ الثاني: التعريف بمصطلحات البحث. وتناولت الدراسة التوجيه من ثلاث مستويات: الأول: المستوى الصوتي: الكلام هنا عن الناحية الأدائية وأحكام التلاوة للكلمات التي انفرد بها أبي عمرو عن بقية القراء، والتماس الحجة لها. الثاني: المستوى النحوي: والكلام فيه عن الخلاف الحاصل في الحركات الإعرابية لمفردات القرآن، وتوجيهه توجيها نحوياً. الثالث: المستوى الصرفي: البنية التركيبية والأوزان الصرفية للفظ مع الاحتجاج لها هو مدار الكلام في هذا المستوى. ومن أبرز النتائج المُتوصّل إليها من خلال هذه الدّراسة ما يلي:  الظواهر الصوتيّة المحضة في قراءة أبي عمرو لمْ تؤثّر في الدلالة أو المعنى، وهي ظواهر مألوفة بسبب لهجات العرب المتعددة والمتنوعة.  كان لأبي عمرو شخصية موسوعية مؤثرة، وذلك من خلال قراءته والتي كان لها صدى واسع وتأثير بارز على كلّ المؤلفات التي عنيت بالقراءات القرآنية، وخاصّة كتب التوجيه وكتب التفسير.""This is a study entitled: Linguistic guidance for the singularities of Imam Abu Amr Al-Basri in the Qur’anic readings. The problem posed is: To what extent did the scholars pay attention to the singularities of Abu Amr al-Basri in reading? And what are the levels of their linguistic orientation of these singularities? The plan to implement it is as follows: The first topic: a conceptual introduction. It is divided into two parts: The first requirement: Abu Amr bin Al-Ala’ Al-Basri; His personal and scientific life. The second requirement: the definition of search terms. The study dealt with guidance from three levels: The first: the vocal level: talking here about the performative aspect and the rulings of recitation of the words that Abi Amr was unique to the rest of the readers, and seeking the argument for it. The second: the grammatical level: the discussion in it about the dispute in the grammatical movements of the vocabulary of the Qur’an, and its grammatical orientation. The third: the morphological level: the structural structure and the morphological weights of the utterance with the invocation of it is the focus of speech at this level. Among the most prominent results obtained through this study are the following:  The pure phonemic phenomena in the reading of Abi Amr did not affect the significance or the meaning, and they are familiar phenomena due to the many and varied dialects of the Arabs.  Abu Amr had an influential encyclopedic personality, through his reading, which had a wide resonance and a prominent impact on all the literature that was concerned with Qur’anic readings, especially guidance books and exegesis books."
مذكرة ماستر
Keywords: التوجيه اللغوي، انفرادات القرّاء، قراءة أبي عمرو البصري، مفردة أبي عمرو، المستويات اللغوية.; Linguistic guidance, readers' singularities, reading Abi Amr Al-Basri, Abi Amr vocabulary, linguistic levels.